Information Technology Capabilities and Innovation Capacities Increasing with Competitive Advantage - SILVIA HENDRAYANTI; Wachidah Fauziyanti; Moh Tamrin (Management Analysis Journal, 2023)
This study aims to examine the effect of information technology capability and innovation capability on culinary UMKM competitive advantage with strategy as an intervening variable. This research was conducted in the city of Semarang. The sampling technique used purposive sampling method. The research data is primary data collected by distributing questionnaires to UMKM owners in the culinary field in Semarang City with a sample of 96 respondents. Hypothesis testing is done using the Path Analysis method. Based on statistical tests, the results show that information technology capability has a significant effect on strategy, innovation capability has a significant effect on strategy, information technology capability has a significant effect on competitive advantage. Innovation capability has a significant effect on competitive advantage, and Strategy has a significant effect on competitive advantage. Micro, small and medium businesses in the culinary field It is suggested to be able to continue to increase the use of information technology in order support business activities and improve the ability to create innovation in product without losing the original product.